2021
DOI: 10.3389/fendo.2021.647864
|View full text |Cite
|
Sign up to set email alerts
|

A Genetic Risk Score Improves the Prediction of Type 2 Diabetes Mellitus in Mexican Youths but Has Lower Predictive Utility Compared With Non-Genetic Factors

Abstract: BackgroundType 2 diabetes (T2D) is a multifactorial disease caused by a complex interplay between environmental risk factors and genetic predisposition. To date, a total of 10 single nucleotide polymorphism (SNPs) have been associated with pediatric-onset T2D in Mexicans, with a small individual effect size. A genetic risk score (GRS) that combines these SNPs could serve as a predictor of the risk for pediatric-onset T2D.ObjectiveTo assess the clinical utility of a GRS that combines 10 SNPs to improve risk pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 80 publications
1
16
0
1
Order By: Relevance
“…The present study demonstrated that a GRS based on six diabetes-related SNPs greatly improved the risk prediction of prediabetes and T2DM compared to a single SNP after adjusting for clinical risk factors. This result is in line with the findings of other studies, wherein the GRS evaluated the cumulative effects of genetic factors [47,48]. While a single GRS model (Model 3) showed a lower predictive ability for prediabetes and T2DM compared to the single models of OSS (Model 2) and BMI (Model 1), combining the three factors (Model 6) prompted a modest increase in the current study.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The present study demonstrated that a GRS based on six diabetes-related SNPs greatly improved the risk prediction of prediabetes and T2DM compared to a single SNP after adjusting for clinical risk factors. This result is in line with the findings of other studies, wherein the GRS evaluated the cumulative effects of genetic factors [47,48]. While a single GRS model (Model 3) showed a lower predictive ability for prediabetes and T2DM compared to the single models of OSS (Model 2) and BMI (Model 1), combining the three factors (Model 6) prompted a modest increase in the current study.…”
Section: Discussionsupporting
confidence: 93%
“…While a single GRS model (Model 3) showed a lower predictive ability for prediabetes and T2DM compared to the single models of OSS (Model 2) and BMI (Model 1), combining the three factors (Model 6) prompted a modest increase in the current study. Miranda-Lora et al [47] suggested that the GRS alone or in combination with T2DM clinical factors increased the power of risk prediction models. Conclusively, the GRS will be helpful for future practical use in improving the prediction of prediabetes and T2DM, and additional susceptibility SNPs will contribute to further strengthening risk prediction models.…”
Section: Discussionmentioning
confidence: 99%
“…After all the conflicts were resolved, 130 articles were included for the full-article screen, and 54 studies were included for data extraction (eFigure 1 in Supplement 1). Details for each individual study are presented in eTables 2 to 5 in Supplement 1. For all 4 meta-analyses, cases and controls were similar in age and sex (Table 1), with limited data available for race and ethnicity across all studies (eTables 6 and 7 in Supplement 1).…”
Section: Resultsmentioning
confidence: 99%
“…34 Genetic risk scores (GRSs), which allow for the assessment of the aggregate genetic risk of a given trait, have demonstrated association of GRSs constructed from variants associated in adults with glycemic traits and/or T2D risk with fasting glucose and measures of b-cell function, [35][36][37] as well as measures of insulin resistance 35,36,38 in youth. Two studies have examined the ability of GRSs to identify children at risk of progressing to T2D; even though the scores were shown to be associated with T2D risk, 36,39 in one of the studies clinical factors such as body mass index (BMI) and family history of T2D had higher predictive utility. 34…”
Section: Candidate Gene Studiesmentioning
confidence: 99%